Technostress and job outcomes: a systematic literature review - Mohd Iqhsan Shahfarie Hj Ibrahim; Zafir Khan Mohamed Makhbul; Abu Hanifah Ayob (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of technology in daily life and tasks has led to a variety of job outcomes. These were previously referred to under various terms and concepts used by past researchers. A Systematic Literature Review (SLR) was conducted and since this phenomenon is still new and in the exploratory phase, this technique will give an overview of the trend shown in past studies as related to impact on job outcomes. Data for this article were gathered from the Scopus and Web of Science databases from 1982 to 2021. Seventy articles were finalized from 269 found at the initial stage through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting method. The study has identified and combined as many as ten terms and concepts into job outcome dimensions and further developed a conceptual framework between technostress and job outcomes. The trend and combination of these dimensions will be a source of reference and guidelines for organizations to formulate intervention measures to reduce the impact of technostress on job outcomes. Meanwhile, further research is recommended to focus on the role of mediating and moderating factors that may also affect job outcomes.